(3QSGdI aj GdeMQes - (3eLghds
(3ChdgG (B:s
.. (3EPG ONd GdeMQe aj jhe GdSHJ jchf GdTJGA TOjO GdQjGM hGdHQOL hbd ajg GdMfWI hGdTYjQ ef fGMjI gLQ hZjQgG hjbY GdehJ aj GdHgGje hGdMejQ (B..s
(3BNQgG (B:s
.. (3EPG GQJaY GdeQjN GTJO GdMQ hEPG GQJaY RNMd GTJO GdHQO hEPG CNP RNd aj GdgHhW GTJO GdMQ hGdeQjN fLe MGQ hRMd fLe HGQO (B..s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdebjGJs